Dietary Supplement Intake and Associated Factors Among Gym Users in a University Community. (2nd January 2018) - Attlee, Amita; Haider, Amina; Hassan, Asma; Alzamil, Noura; Hashim, Mona; Obaid, Reyad Shaker
ABSTRACT: Dietary supplement intake and associated factors among gym users in a university community in Sharjah, United Arab Emirates (UAE), were assessed using a structured, self-administered questionnaire in this cross-sectional study. Adults ( N = 320) from five gyms in the University City of Sharjah participated in this cross-sectional study. The prevalence of dietary supplement intake was 43.8%. Statistically significant associations were found between the use of dietary supplements and sex (47.7% males, 28.1% females; p = .006), as well as weight lifting (88.6% taking supplements vs. 11.4% not taking supplements; p < .001), favoring male gym users. The reasons attributed to the use of dietary supplements varied between the sexes. Male exercisers used supplements to increase or maintain muscles mass, strength, and power and to boost exercise recovery. Females mainly used dietary supplements to increase energy, maintain their health, and prevent nutrition deficiency. Overall, protein supplements (whey proteins [48.6%] and protein powder [45.7%]) were among the most-consumed dietary supplements, followed by multivitamins (38.6%), branched-chain amino acids (36.4%), caffeine (35.0%), and creatine (29.3%). A widespread use of Internet-driven, self-prescribed dietary supplement intake was reported among gym users (60.7%). Only 12.8% of dietary supplement users sought information from dietitians. Practical implications suggest that gym instructors and coaches should be sufficiently trained to be able to provide accurate and scientifically sound information on dietary supplements to the exercisers in gyms in the university environment.